Data is different, and that's why the world needs a new approach to governing cross-border data flows. Issue 5 (13th June 2019) - Aaronson, Susan Ariel
Abstract : Purpose: Companies, governments and individuals are using data to create new services such as apps, artificial intelligence (AI) and the Internet of Things (IoT). These data-driven services rely on large pools of data and a relatively unhindered flow of data across borders (few market access or governance barriers). The current approach to governing cross-border data flows through trade agreements and has not led to binding, universal or interoperable rules governing the use of data. The purpose of this article is to explain the new role of data in trade and to explain why data in trade is different from trade in other goods and services. We then suggest a new approach at the national and international levels. Design/methodology/approach: The author uses a mixed methods approach to examine what the literature says about data as a traded good and or service, examines metaphors regarding the role of data in the economy, and then examines whether or not data is really "traded." Findings: Many countries do not know how to regulate data driven services. There is no consensus on what the appropriate regulatory environment looks like, nor is there a consensus on what are the barriers to cross-border data flows and what constitutes legitimate domestic regulation. Originality/value: This is the first article to explain both the unique nature of data and the ineffectiveness of the trade system to address that distinctiveness.